2022
DOI: 10.3389/fnut.2022.849727
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Antioxidant Indices in Relation to All-Cause and Cause-Specific Mortality Among Adults With Diabetes: A Prospective Cohort Study

Abstract: BackgroundThe potential beneficial effect of individual antioxidants on mortality has been reported. However, the association of overall intakes of dietary antioxidants with all-cause and cause-specific mortality among adults with diabetes remained unclear.MethodsA total of 4,699 US adults with diabetes were enrolled in 2003–2014 in the National Health and Nutrition Examination Survey (NHANES) and followed for mortality until 31 December 2015. The Dietary Antioxidant Quality Score (DAQS) and the Dietary Antiox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…Besides, dietary antioxidants were also reported to be associated with mortality, although not consistently. Wang et al observed that higher intakes of antioxidants were associated with reduced mortality risk from all causes and cardiovascular disease in diabetic adults [ 40 ]. According to other studies, higher intakes of magnesium, zinc, selenium, and vitamins A, C, and E were inversely related to reduced mortality risk [ 41 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, dietary antioxidants were also reported to be associated with mortality, although not consistently. Wang et al observed that higher intakes of antioxidants were associated with reduced mortality risk from all causes and cardiovascular disease in diabetic adults [ 40 ]. According to other studies, higher intakes of magnesium, zinc, selenium, and vitamins A, C, and E were inversely related to reduced mortality risk [ 41 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that high CDAI Food & Function Paper levels reduce the levels of inflammatory factors and lower the risk of various diseases, such as lung cancer, non-alcoholic fatty liver disease, and DM. 3,8,[31][32][33] However, existing evidence of the association between higher dietary antioxidant intake and CKD is limited. This study aimed to address this research gap and provide evidence that adequate antioxidant intake may reduce the incidence of CKD.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with those of previous studies. 6,8 Although the specific reasons for this finding are unclear, it may be because these individuals have higher levels of oxidative stress, and exogenous antioxidant intake appears to be more protective in those with higher innate or acquired ROS-levels. 34 Our results suggest that people at high risk of CKD may benefit more from overall dietary antioxidant intake.…”
Section: Discussionmentioning
confidence: 99%
“…The DAQS is composed of six essential dietary antioxidant micronutrients, namely vitamins A, C, E, Se, Zn and Mg (19) . Each of the six nutrient/mineral intakes was compared with the respective recommended daily intake for US adults.…”
Section: Methodsmentioning
confidence: 99%
“…Total intakes of each nutrient/mineral were calculated by summing from total daily intake from diet and supplemental intake. DAQS was categorised as three groups: low quality (1–2 score), medium quality (3–4 score) and high quality (5–6 score) (19) .…”
Section: Methodsmentioning
confidence: 99%